Enhance Keystroke Dynamic For Online Based System - Teh, Teck Guan (2017)
Current password authentication system was proven not secure enough to protect the information from intruders. A number of researches have been done for the past 25 years, with various methods been used. However, various researches have its own method of collection data and analysis the data. The False Reject Rate and False Accept Rate can be high up to 30 % but overall averages have around 5%. One of the methods suggests is enhancing the current system using keystroke dynamics. Keystroke dynamics is a type of biometric authentication that not requires any special hardware. Beside it is easy to use, as the same routine as normal password authentication. Furthermore, keystroke dynamic has a great potential to replace the existing password system as it doesn’t require any major changes at the current system, with only add in some more fields for the system and have supported software to use capture and match the user’s typing patterns. Therefore, this research proposed an authentication system using keystroke dynamics in order to prevent the system from intruders. A system is developed that consist of two parts which are enrollment and verification. In enrollment part, the user will register into the system by typing necessary information including username, password and the standard phrase. In this part, the user typing time is recorded and a reference template is created. Then, the verification part will take placed in which the match of the similarity between the login and the reference template will be verified based on the threshold set in order to grant the user accessing the system. The proposed system is utilized the Microsoft.NET framework, keyboard and Microsoft IIS. A prototype is developed that consists of 3 main modules, namely Enrollment, Client/Server Connection and, Verification and Retraining. In Enrollment module, the user’s typing data will be collected during the user registration process. The Client/Server Connection module provides a communication medium between the client program and also the system server. Then the user will be identified in the Verification and Retraining Module by comparing the login data with reference template. Any successful login data into reference data is recorded to increase the efficiency of the system. Based on the testing, the system proved that keystroke dynamic authentication system were able to implement in client/server environment. In future, the system can be improved by enhancing the security, performance, and user interface.